A nationwide, cross-sectional, web-based survey on healthcare providers' knowledge about, attitudes toward, and perceived barriers to adherence to clinical practice guidelines for anticancer drug therapy for older patients with cancer in Japan. Issue 1 (January 2023) - Matsuoka, Ayumu; Shimazu, Taichi; Takahashi, Masahiro; Nagashima, Fumio; Nishiyama, Hiroyuki; Fujimori, Maiko; Ando, Yuichi
Abstract: Introduction: In July 2019, in accordance with the Medical Information Distribution Service Manual for Guideline Development 2014, which was based on the Grading of Recommendations Assessment, Development and Evaluation approach, the Japanese Society of Medical Oncology (JSMO) and the Japan Society of Clinical Oncology (JSCO) published clinical practice guidelines (CPGs) on chemotherapy and other drug therapies for older patients with cancer (JSMO-JSCO CPGs). In September 2020, at one year after the publication of these guidelines, a survey was conducted to determine the extent to which they had been disseminated to JSMO and JSCO members and implemented in daily practice. Materials and Methods: This nationwide, cross-sectional, web-based survey was conducted with JSMO and JSCO members. We surveyed the participants' overall awareness of the JSMO-JSCO CPGs, and their knowledge about, attitudes toward, and perceived barriers to adherence to each recommendation using validated questionnaires based on theoretical frameworks used in previous studies (Awareness to Adherence Model, Clinicians' Assessments of Practice Guidelines in Oncology questionnaires, and Knowledge–Attitudes–Behavior Framework). Results: Among JSMO and JSCO members who had been informed of the survey, 1230 responded (response rate: 8.6% and 4.8%, respectively). From these respondents, 107 were excluded because they did not practice anticancer drug therapy at the time of the survey. Of the remaining 1123 eligible participants, 674 (60.0%) were aware of the JSMO-JSCO CPGs before the survey, 492 (73.0%) of whom had read all or part of the guidelines (publications 57.1%, JSMO website 34.8%, and JSCO website 14.0%). Knowledge about, attitudes toward, and barriers to adherence to each recommendation differed widely according to the clinical questions. The most commonly cited barriers were lack of awareness, lack of agreement, lack of evidence, lack of outcome expectancy, patient values and preferences, and patient factors. Discussion: This survey identified different barriers to guideline adherence, including providers' knowledge, attitudes, and external factors, depending on each recommendation. Effective strategies to overcome these barriers can be expected to improve the implementation of the guideline recommendations. Based on the results of this survey, efforts should be made to promote further the use of the clinical guidelines in daily practice.